Limonense Creole English - Portilla-Chaves, Mario (2022)
In the first part, this paper presents a general overview about the sociolinguistic situation of the English-based creole language spoken in Costa Rica, as well asits historic and genealogical relationships. In the second part, a more subjective viewpoint about this language is given from the personal experience of a native speaker of it.